1995
DOI: 10.1139/m95-025
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient effects on growth and armentomycin production in cultures of Streptomyces atmentosus

Abstract: A high-performance liquid chromatographic method for the analysis of armentomycin (L-2-amino-4,4-dichlorobutanoic acid) in culture broths was developed and calibrated using DL-2-amino-4,4-dichlorobutanoic acid synthesized in five steps from methyl acrylate, carbon tetrachloride, and sodium azide. Armentomycin was produced optimally (5–10 mM during 8 days' fermentation) by Streptomyces armentosus in media containing starch, lysine, chloride ions, and a low concentration of phosphate. Production was markedly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…fluorescens in the growth medium. Similar to our results, in other bacteria such as Streptomyces griseocarneus , l ‐lysine enhance antibiotic production such as chlorinated non‐proteic amino acidarmentomycin (He et al. 1995), the polyketide macrolides oleandomycin and spiramycin (Vilches et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…fluorescens in the growth medium. Similar to our results, in other bacteria such as Streptomyces griseocarneus , l ‐lysine enhance antibiotic production such as chlorinated non‐proteic amino acidarmentomycin (He et al. 1995), the polyketide macrolides oleandomycin and spiramycin (Vilches et al.…”
Section: Discussionsupporting
confidence: 88%
“…fluorescens in the growth medium. Similar to our results, in other bacteria such as Streptomyces griseocarneus, L L-lysine enhance antibiotic production such as chlorinated non-proteic amino acidarmentomycin (He et al 1995), the polyketide macrolides oleandomycin and spiramycin (Vilches et al 1990) and b-lactams (Jensen and Demain 1995). Likewise, Cruz et al (1999) observed that chemically defined medium amended with glucose as carbon and L L-lysine as nitrogen source enhanced pyrazoloisoquinolinone (APHE 1-3) antibiotics production.…”
Section: Discussionsupporting
confidence: 87%
“…Surprisingly, none of the carbon sources classified as pentoses, disaccharides, or trisaccharides were catabolized by Streptomyces noursei ATCC 11455 [30]. In contrast to S. noursei ATCC 11455, several Streptomyces have been demonstrated to grow on galactose, xylose, maltose, sucrose, lactose, and raffinose [31][32][33]. There is diversity in carbon sources that can be metabolized by different Streptomyces species.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that streptomycetes are capable of utilizing a wide variety of carbon and nitrogen sources (Kutzner 1986). However, starch is one of the most favourable carbon sources for several Streptomyces species (Doull and Vining 1990; He et al. 1995; Raytapadar and Paul 2001).…”
Section: Discussionmentioning
confidence: 99%